PERKEMBANGAN TATA RIAS PENGANTIN KOTO GADANG SUMATERA BARAT PADA TAHUN 1983 â€“ 2008 - AGUSTINA, NIA (Jurnal Tata Rias, 2012)
ABSTRACT Nia Agustina, has made through, persistent and on going research through consistent and meticulous observation of the progress, changes and development of the traditional wedding ceremony, specializing in the make up titled the : â€œPerkembangan Tata Rias Pengantin Koto Gadang, Sumatera Barat Dari Tahun 1983 Sampai Dengan 2008â€. The methodology of the research is the qualitative method at the Koto Gadang, Sumatera Barat Area in the southern part of Sumatera, since August 2008 until January 2009. the purpose of the qualitative research is to meet the study and program taken â€œProgram Studi Tata Rias, Jurusan Ilmu Kesejahteraan Keluarga, Fakultas Teknik Universitas Negeri Jakartaâ€™ (Beauty and beautician study, majoring in the wedding ceremony of the faculty of family health and sciences, the state University of Jakarta). The qualitative research is particularly and exclusively selected to study in depth, thus observing the progress made during the period. The observation and study has no intention to prove any specific theory or special hypothesis. Thus the research is merely to seek, identify and illustrate the progress, changes and development of the wedding ceremony. Thus analyzing the changes and progress of the wedding ceremony. The analyses would encompass and specifically on the attire and make up become the main purpose. Key word : Progres improvement, Traditional Wedding Ceremony, Koto Gadang of North Sumatra. ABSTRAK Nia Agustina, Penelitian Perkembangan Tata Rias Pengantin Koto Gadang, dari tahun 1983 sampai dengan tahun 2008. (Suatu Penelitian Kualitatif di daerah DKI Jakarta bulan Agustus 2008 sampai Januari 2009) Skripsi, Jakarta, Program Studi Tata Rias, Jurusan Ilmu Kesejahteraan Keluarga, Fakultas Teknik, Universitas Negeri Jakarta. Penelitian ini bersifat kualitatif yaitu tidak bermaksud untuk menguji hipotesis tertentu tetapi hanya menggambarkan apa adanya tentang suatu, gejala, variabel atau keadaan. Tujuan dari penelitian ini yaitu untuk menganalisa perubahan dan perkembangan tata rias pengantin Koto Gadang dari tahun 1983 sampai 2008. Data diperoleh melalui teknik pengamatan, wawancara, dokumentasi dan studi kepustakaan yang dilakukan di Anjungan Sumatera Barat Taman Mini Indonesia Indah dan di sekitar DKI Jakarta. Analisa data dilakukan melalui analisa data model interaktif yang terdiri dari alur kegiatan yang terjadi secara bersamaan yaitu pengumpulan data, reduksi data, penyajian data, penarikan kesimpulan dan interprestasi. Kata Kunci: Perkembangan, Tata Rias Pengantin, Koto Gadang Sumatra Barat